Self-Consolidating Concrete : Applying What We Know - Daczko, Joseph A. (London ; New York : CRC Press, 2012)
"Self-consolidating concrete (SCC) is an innovative material used successfully throughout the world. It is a highly flowable, non-segregating concrete that can spread into place, fill the formwork, and encapsulate the reinforcement without any mechanical consolidation, improving the overall efficiency of a concrete construction project. SCC mixtures are highly fluid, yet their flowing properties can be adapted for a range of applications and allow practitioners to select and determine levels of filling ability, passing ability, and stability. Presenting a basis for consistently producing and applying SCC in a regular production environment, this book is written from the perspective of the concrete practitioner. It uses descriptions and case studies throughout, as examples of specific types of applications, to identify where the practitioner needs to focus attention."--Back cover.
-- Introduction, History, and Acceptance of SCC -- Benefits and Limitations of SCC -- Fresh Properties and Test Methods -- Hardened Properties of SCC -- Powders and Aggregates -- Chemical Admixtures -- Considerations Prior to Mixture Proportioning -- Proportioning SCC Mixtures -- Mixture Qualification -- Concrete Batching and Mixing -- Quality Control of SCC Materials and Mixtures -- Transport, Placement, Finishing, and Curing -- Troubleshooting SCC Performance -- Implementation and Training -- Applications of SCC.
Includes bibliographical references and index.
Keywords: Self-consolidating concrete; Concrete -- Mixing